Impact of Monetary Policy Interaction on Economic Growth and Human Development Index - A. Mahendra; Witya Shalini (PT. Riset Press International, 2026)
The phenomenon in this study discusses the monetary policy that has not been able to maintain the stability of the Indonesian economy caused by the global economic crisis in 2008, changes in the United States' monetary policy, one of which is by lowering its interest rates to 0.25% and the fall in the prices of plantation and mining commodities where as much as 60 to 70% of Indonesia's economic growth comes from exports of plantation and mining commodities in the period 2013-2015. This study aims to analyze and examine the interaction of monetary policy instruments, including SBI and money supply, on Indonesia's Gross Domestic Product and Human Development Index. The type of research used is explanatory research with a quantitative approach using the Vector Autoregression (VAR) model. The data collection technique in this study used documentation. The data used in this study is secondary and time series. The data sources used in this study were from the Statistics Indonesia and Bank Indonesia. The results of this study indicate that 1). Interaction with GDP, where the SBI variable interacts negatively, while the Money Supply variable interacts positively 2). Interaction with HDI, where the SBI variable interacts negatively, while the Money Supply variable interacts positively. The main contribution of this research is emphasizing the importance of interactions between monetary policy instruments and their coordination with other policies in promoting inclusive growth. Furthermore, this research enriches the literature by linking monetary policy to the Human Development Index, which reflects societal well-being. Therefore, the findings can serve as a basis for governments and central banks in formulating policies that are oriented not only toward economic stability but also toward sustainably improving people's quality of life.